(untitled) (Research, Society and Development, 2021)
The Intensive Care Units (ICU) are complex environments, with an apparatus of equipment and materials, intended for the maintenance of care for patients in serious condition. The Neonatal Care Units (NICU) are spaces designed to assist babies who are premature, with low birth weight or even those born with a health problem. Despite this environment, being surrounded by a high demand for services, it ends up demanding speed and fluidity from its workers, as a result, the service itself becomes mechanized. This study aims to reflect on the importance of humanization in the care process in the NICU and its importance for the quality of care provided to the newborn. This is a literature review of the narrative type. Studies primarily show humanistic care as an indispensable factor in the hospital environment, and the inclusion of the family triad as an approach to treatment. It is concluded that humanization in care begins with active listening both from servers in their workplaces and between professionals and patients’ parents, analyzing the signs and expressions of the patient that can help in better handling related to hygiene, changing position, and thus, using comfort methods to create a welcoming environment for the newborn and with the inclusion of family members being essential to improve the clinical condition.